Neurone: Online Inquiry Experimentation System - Gonzalez-Ibanez, R; Gacitua-Vasquez, D (John Wiley and Sons Inc, 2017)
In this poster we introduce NEURONE, an open source web-based system for assessing online inquiry competences (OIC). NEURONE is a fully customizable solution that can be adapted to different research conditions through eight modules and a set of tools. To date, NEURONE has been successfully used to implement, deploy and run an online assessment contextualized in a pretest-posttest study design, in which nearly 1400 sessions were conducted with 350 elementary school students in their early adolescence. Copyright © 2017 by Association for Information Science and Technology
Keywords: assessment; elementary schools; information literacy; online inquiry competences; tests